2019
DOI: 10.1134/s0016702919110065
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Selenium Level and its Enrichment Dynamics in Seawater Intrusion Area along the Northern Coastal Zones of Shandong Province, China

Abstract: The variation of groundwater properties caused by seawater intrusion, such as OH-, TDS, can potentially affect the groundwater Se levels. But there are no researches detailing the mechanism of groundwater selenium characteristics in seawater intrusion areas along coastal zones. Buzhuang town has been selected for study and groundwater is sampled to discuss the behavior of groundwater selenium with the intrusion of seawater. The groundwater Se levels range from 1.43 to 15.60 μg/L, with an average of 6.23 μg/L. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The groundwater parameters of Cl − and TDS are often used to adequately classify water samples in sea water intrusion, and TDS > 1000 mg/L or Cl − > 250 mg/L is a sign of sea water intrusion (Liu et al 2018;Chen et al 2019b). The average of Cl − and TDS in the area underlain by Quaternary sediment indicates an obvious sea water intrusion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The groundwater parameters of Cl − and TDS are often used to adequately classify water samples in sea water intrusion, and TDS > 1000 mg/L or Cl − > 250 mg/L is a sign of sea water intrusion (Liu et al 2018;Chen et al 2019b). The average of Cl − and TDS in the area underlain by Quaternary sediment indicates an obvious sea water intrusion.…”
Section: Resultsmentioning
confidence: 99%
“…OH − and F − have the same radius and recharges, and groundwater OH − often exchanges F − in minerals (Wang et al 2015;Chen et al 2019b). It is widely documented that the groundwater F − concentration increases with increasing pH (Ma et al 2014;Wang et al 2015;Guo et al 2015;Chen et al 2019b).…”
Section: The Correlation Between Groundwater Fluorine Levels and Othe...mentioning
confidence: 99%
See 1 more Smart Citation
“…The WHO suggested that the average daily intake of Se be ∼30–50 μg day –1 . Inadequate or excess Se intake will cause adverse effects on the human body (safety range of 40–400 μg day –1 ). , Some researchers tried to remediate groundwater contaminated with Se­(VI) and Se­(IV) with Bio-PRBs and achieved a satisfying removal effect.…”
Section: Bio-prbs For Remediation Of Soil and Groundwatermentioning
confidence: 99%